Hubungan Stigma Sosial dengan Psychological Well-Being pada Wanita Dewasa Awal Lajang Beretnis Minangkabau - Listy, Whindy; Dwatra, Free Dirga (Lembaga Yasin AlSys, 2025)
Early adulthood is a life stage closely associated with the formation of social relationships, including marriage, which remains a dominant norm and priority in many societies. However, the past decade has seen a rise in the number of early adult women choosing to remain single, including among the Minangkabau ethnic group. This phenomenon is often accompanied by negative social stigma, such as being labeled “perawan tua” (old maid), which may affect an individual’s psychological well-being. Psychological well-being reflects a person’s positive state in terms of self-acceptance, personal growth, and the ability to build healthy social relationships. This study aims to examine the relationship between social stigma and psychological well-being among unmarried early adult Minangkabau women. A quantitative approach with a correlational design was employed. The sample consisted of 100 unmarried women aged 25–49 years, selected through purposive sampling based on the Lemeshow sample size formula. Research instruments included a social stigma scale and a psychological well-being scale, analyzed using Pearson’s correlation test. The results revealed a significant positive correlation between social stigma and psychological well-being (r = 0.620; p = 0.001). These findings suggest that higher perceived social stigma is associated with higher psychological well-being, indicating the presence of adaptive mechanisms among single Minangkabau women in responding to stigma. Such mechanisms may foster psychological resilience and self-acceptance. This study contributes to the literature on cultural and gender psychology and offers practical implications for the development of interventions that strengthen self-acceptance and social resilience.